Sociālistiskās tiesību doktrīnas ietekme uz privātīpašuma tiesību institūtu Latvijā 1940. - 1990.g. - Slūka, Dagnis (Latvijas Universitāte, 2006)
In the work there is researched the influence of socialistic law doctrine on the private law institution in Latvia in 1940. – 1990. The aim of the work is to prove that the influence of the socialistic law doctrine on the private law in Latvia is not valued only negatively, but there have been also positive aspects. For achieving the presupposed aim there are viewed the development of the socialistic law doctrine, when in the ancient Greece philosopher works there have been appeared characteristic ideas to the socialistic law doctrine, till the time when Latvia regained the independence. A special attention is drawn to the soviet law, investigating the idea of the socialistic law doctrine and the influence of the cognition to the concrete private law branches, as well as displaying both negative and positive influence aspects. In the result of the research there was concluded that not looking at this, that the idea of socialistic law doctrine including in the legislation with an aim to provide social equality limiting disclosure of individual freedom and rights, still its influence on the private rights has a positive character too.
Influence of Socialist doctrine of Rights on the institution of privater property Rights in Latvia during the period of 1940 - 1990
Keywords: Tiesības